Hubungan Derajat Aktivitas Penyakit Dengan Status Kesehatan Pada Pasien Systemic Lupus Erythematosus (SLE) di Komunitas Odapus Lampung - Dwi Sebtelia; Festy Ladyani; Rina Kriswiastiny; Firhat Esfandiari (Universitas Malahayati, 2022)
ABSTRACT Systemic Lupus Erythematosus (SLE) is a complex systemic autoimmune disease characterized by increased production of autoantibodies, with inflammation of various organs. To determine the relationship between the degree of disease activity and health status in Systemic Lupus Erythematosus (SLE) patients in the Lampung ODAPUS Community in 2020. An analytic survey with cross-sectional, using total sampling. The subjects are 40 patients in the Lampung ODAPUS Community in 2020. The study found patients with a degree of mild disease activity were 5 respondents (12.5%), and severe 35 respondents (87.5%). Good health status 13 respondents (32.5%), bad 27 respondents (67.5%). The results of the Chi-Square test analysis showed a p-value=0.000 (p <0.015), which means that there is a significant relationship between the degree of disease activity and health status. There is a relationship between the degree of disease activity and health status in Systemic Lupus Erythematosus (SLE) patients in the Lampung ODAPUS Community in 2020 (p-value<0,05). Keywords: Degree of Disease, Health Status, SLE ABSTRAK Systemic Lupus Erythematosus (SLE) merupakan penyakit autoimun sistemik kompleks penandaannya pada peningkatan produksi autoantibodi dan inflamasi pada organ. Tujuan untuk mengetahui hubungan derajat aktivitas penyakit dengan status kesehatan pada pasien Systemic Lupus Erythematosus (SLE) di Komunitas ODAPUS Lampung tahun 2020. Metode bersifat analitik secara cross sectional, menggunakan total sampling. Responden penelitian seluruh pasien Lupus di Komunitas ODAPUS Lampung sebanyak 40 orang. Penelitian didapatkan pasien dengan derajat aktivitas penyakit ringan 5 responden (12,5%), berat 35 responden (87,5%). Status kesehatan baik 13 responden (32,5%), buruk 27 responden (67,5%). Hasil analisa uji Chi Square p-value=0,000 (p<0,015) terdapat hubungan bermakna derajat aktivitas penyakit dengan status kesehatan. Terdapat hubungan derajat aktivitas penyakit dengan status kesehatan pada pasien Systemic Lupus Erythematosus (SLE) di Komunitas ODAPUS Lampung tahun 2020 (p-value<0,05). Kata Kunci : Derajat Penyakit, Status Kesehatan, SLE